The Magic Role of Kim Nam Joon as a Leader of BTS in Conquering the American Market - Iin Rachmawati (Rubikon : Journal of Transnational American Studies, 2022)
Bangtan Sonyeondan or popularly known as BTS is a South Korean phenomenal group. The massive popularity of BTS all over the world cannot be separated from the magic role of their leader, Kim Nam Joon. This research tried to explore Kim Nam Joon’s role in regard to BTS's global popularity. This research used a qualitative descriptive method by using Khan, Nawaz & Khan’s leadership theories and styles as well as used Brown’s audience involvement approach to analyze the data. The result showed that there are four major reasons for Kim Nam Joon’s influence over BTS's success: Kim Nam Joon marked the beginning of BTS, Kim Nam Joon’s compassion and dedication, Kim Nam Joon’s powerful speech, and Kim Nam Joon’s leadership role towards teamwork. Moreover, there was also the fact that several non-BTS American fans tend to become ARMY after they knew about Kim Nam Joon’s leadership role. This is interesting because not all BTS’s fans become ARMY from enjoying BTS songs and performances.